The Importance of Law Enforcement Based on Progressive Law in Realizing Community Welfare - Halim, Chandera; Patria Setyawan, Vincentius (LPPM Universitas Ekasakti Padang, 2024)
Progressive Law emerged from Satjipto Rahardjo's idea of ​​seeing the worrying reality of law enforcement in Indonesia. The law tends to favor the strong and oppress the weak, sharp downwards but dull upwards. This article discusses the importance of having behavior based on Progressive Law in law enforcement. The method used in writing this article is a normative legal research method with a conceptual approach. The results of this research are that law enforcement that improves the welfare of the people in the style of Progressive Law will be formed if law enforcement officers have progressive law enforcement behavior. The meaning of progressive behavior is law enforcement that is sensitive to the realization of the values ​​of justice, and is not confined solely to the formulation of the text of the law. Such law enforcement will create justice, benefit and welfare for society.